The Difference of Authority between Satpol PP and Polri in Creating General Involvement - Tri Suhartanto; Indra Perwira (International Journal of Science and Society, 2020)
This study aims to analyze the differences in law enforcement authority between Civil Service Police Unit (Satpol Pamong Praja/ Satpol PP) and Indonesian National Police (Polri) in creating public order and peace of society and how the differences could cause an overlap in their implementation. The research method used is normative juridical legal research using a statutory, conceptual, and comparative approach. The results showed that differences in law enforcement authority between Satpol PP and Polri are in creating public order and peace of society. Satpol PP has an authority to maintain public order, while the National Police is more concerned with maintaining domestic security; Meanwhile, in carrying out their duties, the Satpol PP often overlaps and clashes with other law enforcers, especially the National Police. It cannot be denied that it often happens that the National Police finally have to become a "fire brigade" when carrying out their duties. The Satpol PP has to clash with the community, which then arises an anarchic situation. When in situations that could lead to further disturbance in security and public order, the National Police finally intervened. What often happened was that the National Police collided with the community because of the anarchist situation that had developed too far.